(untitled) (Revista de História Regional, 2007)
The historicity of the regions and the regionalist ideology putted to use by the dominant classes are the subject of this text. The purpose is discuss the results of this situations over the history teaching, and propose attitude changes that have coerence with a methodological and political renovation, relationed to this problems.